Investor Confidence and the Growth of Reits in Kenya - Thuo, Daniel; O. Onyuma, Samuel (Journal of African Real Estate Research, 2024)
The introduction of REITs at the securities market was intended to broaden capital markets, allowing them to be used to raise funds for affordable housing while also serving as an alternative investment choice. However, since its introduction, Kenya’s REITs market has experienced slow development and information is scant on how investor sentiments may influence performance of REITs. The objective of this study was to examine how investor sentiments influence performance of REITs in Kenya. Predictive correlational research design was employed while target population comprised of Fund Managers, Stock Brokers and Investment Banks and Property Developers. Stratified random sampling was used to determine a representative sample size. A structured questionnaire was used to collect primary data. To summarise the findings, descriptive statistics were employed. Inferential statistics such as the Structural Equation Modelling which incorporated factor analysis, regression analysis and path diagrams were used to test the hypothesized relationships at 5% significance level. The findings Results show that there exists a positive significant influence of investor sentiments on the performance of REITs in Kenya. The study concludes that investor sentiments majorly risk and return are influencing the performance of the REITs market in Kenya, leading to REITs unexpected performance. Continuous engagement sessions between securities market regulatory authority, REITs Association of Kenya, and investors will enhance market confidence, thus lowering the risk-return sentiments. The study recommends that the Capital Markets Authority review the existing market legislation that governs the listing of REITs especially policies on tax for issuance of REITs. In conjunction with the ministry of finance, CMA should consider exempting stamp duty which is charged during the transfer of property into a REIT firm.